Path Analysis of the Effect of Biological and Social Factors on the Case of Breast Cancer - Nunik Ike Yunia Sari; Estin Gita Maringga; Wuri Widi Astuti (JURNAL INFO KESEHATAN, 2019)
Breast cancer is the number one cancer as the cause of death in women in developed and developing countries. Breast cancer has the highest case in women in 161 countries. The objective of this study is to analyze the influence of biological and social factors on breast cancer cases in the Public Hospital of Kediri, East Java. The research design was analytic with a retrospective cohort approach. The research sample of 105 respondents used simple random sampling. Data collection was with medical records in January-December, 2017. Data analysis used the path analysis test. The test results obtained breast cancer is influenced by a history of hereditary breast cancer (b=0.17, p=0.001); menopause age (b=0.17, p=0.001); family planning history (b=0.11, p=0.014); parity (b=0.08, p=0.031); age (b=0.21, p=0.001); income (b=0.21, p=0.001). Parity was influenced by income (b=0.45, p <0.001). The age of menopause was influenced by a history of hereditary breast cancer (b= 0.31, p <0.001); family planning history (b=0.13, p=0.13); and age (b=0.10, p=0.01). It can be concluded that the case of breast cancer was directly influenced by hereditary cancer, family history of birth control, age, parity, menopausal age, and income. Also, breast cancer was indirectly affected by income through parity; and hereditary history of breast cancer, family planning history, and age through menopause.